Neck and trunk kinematics and electromyographic activity during judo backward breakfalls - Koshida, S.; Matsuda, T. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
The purpose of this study was to demonstrate the neck and trunk angle time curves as well as electromyographic (EMG) activities during a judo backward breakfall in both experienced and novice judokas. Six experienced and four novice judokas volunteered to participate in the study. Three-dimensional kinematic and EMG data were collected while participants performed five sets of backward breakfalls at their own speed. We demonstrated neck/trunk angle time curves and muscle activation profiles during judo breakfalls. The results showed that there were no significant differences in the variables between experienced and novice judokas, which suggests that even short-term judo practice improves backward breakfall skills and may help prevent injury.